An ESR study on amorphous NiFe films - (:unkn) unknown (ELSEVIER SCIENCE BV, 1997)
Amorphous Ni90Fe10 alloy films with thickness 500 Angstrom and 2000 Angstrom deposited on quartz substrates by flash evaporation method have been studied by electron spin resonance (ESR) technique at x-band. The ESR spectra were taken as a function of both temperature and the applied magnetic field whose direction was varied from normal to parallel with respect to the film plane. The field derivative absorption line mainly consists of two major peaks for the thicker film and only a single major peak for the thinner one. The spectra have been analyzed by using the classical spin wave resonance (SWR) theory and the magnetic parameters of the system have been deduced. The surface anisotropy energy with uniaxial and biaxial terms have been used to simulate the experimental spectra. It has been found that noncrystalline nature of the sample considerably effects the magnetic behavior. The exchange stiffness constant was found to be seriously reduced compared to those of the polycrystalline films in the literature. However with room temperature aging, this value has increased visibly. Surface anisotropy has been determined to have an easy-plane character.
Keywords: ESR; NiFe films